Antimicrobial enzymatic biofuel cells. Issue 99 (27th November 2020) - Xiao, Xinxin; Ryan, Michael P.; Leech, Dónal; Zhang, Jingdong; Magner, Edmond
Abstract : A compact antibiotic delivery system based on enzymatic biofuel cells was prepared, in which ampicillin was released when discharged in the presence of glucose and O2 . Abstract : A compact antibiotic delivery system based on enzymatic biofuel cells was prepared, in which ampicillin was released when discharged in the presence of glucose and O2 . The release of ampicillin was effective in inhibiting the growth of bacterium Escherichia coli as confirmed by ex situ and in situ release studies in culture media.